Classical open lumbar laminectomy and discectomy for disc herniations among manual labourers in India - Chellarapu, Surendra Kumar; Kadali, Satya Vara Prasad; B., Raja Sekhar; B. V. S., Raman (International Journal of Research in Medical Sciences, 2017)
Background: Lumbar disc herniations are most common at L4/5 and L5/S1 levels and this is most prevalent condition among manual laborers. The aim of the study to analyze the clinical presentation, age and sex distribution, immediate postoperative complications and long-term complications/recurrence of symptoms and to formulate recommendations to avoid complications and recurrence of symptoms. Methods: This is a retrospective study which includes 250 patients operated for lumbar disc herniations at L4/5 and L5/S1 levels. A detailed history of presenting complaints, clinical examination and corresponding findings on imaging are correlated. In all these patients, there was severe symptomatology with failed conservative management which necessitated classical open lumbar laminectomy and discectomy. These patients were followed for a period of 5 to 10 years. Results: Assessment of outcome was done using the modified Macnab criteria. The overall success rate was 96% in our series. Post operatively, 9.2% of them experienced localized low back pain which is mild to moderate and being treated with NSAIDS and exercises. 2.4% developed residual disc herniation or hypertrophic fibrotic scar at the operated site which needed surgical intervention. 2% developed spondylolysis and spondylolesthesis at the level of previous surgery, and 4.4% developed adjacent disc herniations. Conclusions: The overall success rate was 96% in our series. In addition to removal of herniated disc other compressing elements like hypertrophied Ligamentumflavum, facet arthropathy and narrowed spinal canal diameter are also addressed with open procedure. To prevent later complications, these patients are supposed to avoid strenuous work, lifting weights, torsion and jerky movements, faulty posture at work and rest, gait training, crouching, sitting on the floor and haunches.